Effects of Friction Stir Welding Parameters on Hardness of Welded Al 6082 and Al 8011 Plates - Kumar Upadhyay, Dushyant; Pachauri, Praveen; P. Dwivedi, S.; Sharma, Satpal (International Journal of Engineering and Technology, 2018)
Aluminum alloy 6082 and 8011 were welded using friction stir welding technique on milling machine. Tool speed, Tool shape and Cutting fluid are considered as input parameters, while hardness of weld samples was considered as response. Taguchi design with L9 orthogonal array was employed to obtain optimum input parameters for better hardness. Hardness (6082-8011) is better for brine solution and kerosene with minimum and maximum tool speed and least for lubricant oil at any tool speed. Hardness (6082-8011) is better for kerosene and brine solution with square and triangular tool shape but least for lubricant oil with triangular tool shape.Â Â